RMU (PJIA) UiTM Terengganu research grant financial management system (R-GRANT) / Nordiyana Ahmad Marzuki - Ahmad Marzuki, Nordiyana (2014)
This research aims to ease the researchers in order to manage their research grant and also for the staff of Research Management Unit (RMU) which is to effectively keep track of researcher’s financial records. Currently, Research Management Unit used manual form to manage all the processes that had been involved in their unit. Besides that, they also need to consult for Treasurers if they need any latest data especially data that involved with expenses of the researchers. Therefore, R-Grant is develop in order to solve these current problems. The evaluation part has been done with 10 respondents which is three of them are from experts and seven of them are lecturers. The purpose of interview with experts is to know about the current problem that they have and want to know either R-Grant can help them to solve their problem or not. There are five constructs which are user interface; usefulness, ease of use, ease of learning, satisfaction. Construct with the highest result is regarding the satisfaction with seven respondents are strongly agreed with it and mode for this construct is 5. The highest mean based on user feedback for this construct is item E3 (Mean = 4.5, SD = 0.85). This indicates that, the respondents are satisfied with this system because they need this system in order for them to manage their works. Last but not least, R-Grant can help staff of RMU to overcome the current problem that they have as well as have a systematic way to manage the data. There are few suggestions for construction improvement to enhance the usability and functionality of the R-Grant web based system in the future.